Towards a Ḥaḍramitic lexicon: lexical notes on terms relating to the formulary and rituals in expiatory inscriptions - Prioletta, Alessia (Proceedings of the Seminar for Arabian Studies, 2014)
Although the corpus of Hadramitic inscriptions is highly fragmented both chronologically and geographically, its grammatical system and above all its lexicon display unique traits that make it of particular interest to scholars. These traits are especially well defined in the textual genre of the expiatory inscriptions since they display a distinctive formulary and ritual lexicon compared to the textual counterparts in the other South Arabian kingdoms. The study focuses, in particular, on the lexical analysis of some key terms that appear in the fixed formulas within which these inscriptions are structured. The lexicon of these texts is characterized by many unique features compared to the other ASA languages and, on a broader level, combines isoglosses with the Southern Semitic languages, archaisms that recall Akkadian, and a more typically Central Semitic lexicon. These elements still await full analysis and systematic organization into a comparative Haçlramitic lexicon that will allow scholars to pursue broader studies on the position of Haçlramitic within the Ancient South Arabian and Semitic in general.